2015
DOI: 10.1038/ng.3333
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed neuroblastomas show frequent RAS-MAPK pathway mutations

Abstract: The majority of neuroblastoma patients have tumors that initially respond to chemotherapy, but a large proportion of patients will experience therapy-resistant relapses. The molecular basis of this aggressive phenotype is unknown. Whole genome sequencing of 23 paired diagnostic and relapsed neuroblastomas showed clonal evolution from the diagnostic tumor with a median of 29 somatic mutations unique to the relapse sample. Eighteen of the 23 relapse tumors (78%) showed mutations predicted to activate the RAS-MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
483
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(552 citation statements)
references
References 41 publications
41
483
2
6
Order By: Relevance
“…In addition, similar to previous studies (37,39), we identified some unique aberrations in the primary tumor that were no longer present in the relapse samples. These aberrations may tell us about their minor impact concerning driving the tumor cell progression and chemoresistance.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, similar to previous studies (37,39), we identified some unique aberrations in the primary tumor that were no longer present in the relapse samples. These aberrations may tell us about their minor impact concerning driving the tumor cell progression and chemoresistance.…”
Section: Discussionsupporting
confidence: 86%
“…Temporal heterogeneity concerning copy-number changes and gene mutations was reported in neuroblastoma (37)(38)(39). In line with the studies performed on matched primary and relapse neuroblastomas, despite a decrease in subclonal copynumber changes in the relapse samples compared with the primary tumors (39), a number of de novo aberrations were found in the relapse samples (37,39).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It has been reported that recurrent mutations affect pathways such as focal adhesions, Rac/Rho, RAS-MAPK, and YAP in advanced and relapsed neuroblastomas. 3,[40][41][42] Among these pathways, the Rac/Rho pathway is pertinent to the current knowledge of the NDPK-A network.…”
Section: Ndpk-a-relevant Molecular Determinants Of Neuroblastoma Metamentioning
confidence: 99%
“…Therefore, NB (and others pediatric cancers) can be compared with resistant to immune checkpoint inhibitors in adult cancers and need to be treated as such. First, while pediatric tumors demonstrate low mutation burdens at diagnosis, increases in mutation frequency can be enhanced after exposure to chemotherapy or radiotherapy [6,7]. In addition to increase neoantigens, radiation may increase immune response to checkpoint blockade as localized radiation along with checkpoint blockade resulted in an abscopal effect with regression of metastatic lesions outside of the radiation field [8].…”
Section: Immunotherapy Of Neuroblastomamentioning
confidence: 99%